Axiological Approach in Implementing Basic Training for Civil Servant Candidates, Curriculum for State Administration Institution Regulations Number 1 of 2021 - Marantika, Jerry; Ofianto, Ofianto; fitrisia, Azmi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
In the study of philosophy, the term axiology is usually defined as a field (philosophy) that investigates values, including the purpose of obtaining knowledge. CPNS Basic Training is a process of instilling good values ​​and adapting these values to become a character that civil servants or state civil servants should have. The values taught are contained in the Learning Agenda which consists of nationalism values in Agenda I, Moral values (Service Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, Collaborative) in Agenda II, cultural and ethical values using digital media in Agenda III. This research was conducted to determine the training implemented so that CPNS are able to behave and act professionally in managing the challenges and problems of socio-cultural diversity using a whole of government or one government perspective which is based on the basic values ​​of Civil Servants based on their position and role in the Unitary State of the Republic of Indonesia (NKRI) in every implementation of his/her duties as a public servant as a concrete manifestation of defending the country as a Civil Servant.